Using dispute settlement partnerships for capacity building: Bangladesh's triumphant experience at WTO DSU. Issue 1 (25th January 2019) - Bahri, Amrita; Ali, Toufiq
Abstract : Purpose: World Trade Organisation grants rights to its members, and WTO Dispute Settlement Understanding (DSU) provides a rule-oriented consultative and judicial mechanism to protect these rights in cases of WTO-incompatible trade infringements. However, the DSU participation benefits come at a cost. These costs are acutely formidable for least developing countries (LDCs) which have small market size and trading stakes. No LDC has ever filed a WTO compliant, with the only exception of India-Battery dispute filed by Bangladesh against India. This paper aims to look at the experience of how Bangladesh – so far the only LDC member that has filed a formal WTO complaint – persuaded India to withdraw anti-dumping duties India had imposed on the import of acid battery from Bangladesh. Design/methodology/approach: The investigation is grounded on practically informed findings gathered through authors' work experience and several semi-structured interviews and discussions which the authors have conducted with government representatives from Bangladesh, government and industry representatives from other developing countries, trade lawyers and officials based in Geneva and Brussels, and civil society organisations. Findings: The discussion provides a sound indication of the participation impediments that LDCs can face at WTO DSU and the ways in which such challenges can be overcome with the help of resources available at the domestic level. It also exemplifies how domestic laws and practices can respond to international legal instruments and impact the performance of an LDC at an international adjudicatory forum. Originality/value: Except one book chapter and a working paper, there is no literature available on this matter. This investigation is grounded on practically informed findings gathered with the help of original empirical research conducted by the authors.